The Role of Forums in Enhancing Vocabulary Acquisition in English as Foreign Language Classrooms - Vedaschi Ozzola, Matias (Research in Social Sciences and Technology, 2025)
This study investigated the effectiveness of online forum-based collaborative learning versus traditional instructional methods for vocabulary acquisition among English as a foreign language learners. Twenty-one first-year translation and interpreting students participated in a comparative study examining two distinct vocabulary teaching approaches. For tourism vocabulary, students engaged in collaborative forum activities comprising writing descriptive texts and responding to peers’ posts using 15 target lexical items. For media vocabulary, students received traditional instruction through individual exercises and instructor-led activities. The delayed assessments revealed significant differences in vocabulary retention. Students demonstrated a 62% lexical utilization rate following forum-based instruction compared to 35% following traditional methods, representing a 75.5% improvement. The forum-based approach facilitates functional lexical acquisition with appropriate semantic and pragmatic deployment. These findings support sociocultural theory and the interaction hypothesis, suggesting that collaborative forum environments create effective digital zones of proximal development, where meaningful peer interactions enhance vocabulary learning. This study provides empirical evidence that asynchronous online forums significantly outperform conventional vocabulary instruction by promoting deeper lexical processing through collaborative meaning negotiation.